1991
DOI: 10.1073/pnas.88.19.8700
|View full text |Cite
|
Sign up to set email alerts
|

T-cell receptor alpha chain plays a critical role in antigen-specific suppressor cell function.

Abstract: Antigen-specific suppressor T-ceil hybridomas release soluble suppressor factors (TsF) in the supernatant that modulate both in vivo delayed-type hypersensitivity and in vitro plaque-forming cell responses in an antigen-specific manner.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
13
0

Year Published

1992
1992
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(15 citation statements)
references
References 31 publications
1
13
0
Order By: Relevance
“…2). These findings may explain previous observations by other investigators that TCRB-expression variants of hapten-or peptide-specific Ts hybridomas do not express TCR, but could release TsF activity (8,25).…”
Section: Discussionsupporting
confidence: 77%
See 1 more Smart Citation
“…2). These findings may explain previous observations by other investigators that TCRB-expression variants of hapten-or peptide-specific Ts hybridomas do not express TCR, but could release TsF activity (8,25).…”
Section: Discussionsupporting
confidence: 77%
“…It was also found that antisense oligonucleotide corresponding to TCR Va prevented the formation of TsF activity by a Ts hybridoma (7). Kuchroo et al (8,9) developed a series of TCRa-expression variants of Ts hybridomas, and demonstrated that transfection of TCRa cDNA from one Ts hybridoma into the TCRa-f3+ clone of another Ts hybridoma resulted in the formation of TsF activity of the former. These results collectively suggest that a product of TCRa cDNA is TsF or its subunit.…”
mentioning
confidence: 99%
“…This would help explain the development of colitis in TCR ␣-chain-deficient mice (36, 37), as well as in other TCR Tg mice backcrossed onto RAG-2-deficient mice (34,38,39). Loss of the TCR ␣-chain was associated with the concomitant loss of suppressor activity of Ag-specific T suppressor cell lines (40).…”
Section: Discussionmentioning
confidence: 99%
“…In the past several years though, investigators working in several distinct antigenic systems have unequivocally demonstrated the presence of conventional ac3 TCR on Ts hybridomas and clones (23,56,59). Recent studies strongly support a longstanding hypothesis that these suppressor factors are comprised, at least in part, of conventional TCR polypeptides (21,22,24,59). These findings have rekindled an interest in exploring the potential of antigen-specific immunosuppression for the therapy of autoimmune disease and transplant rejection.…”
Section: Discussionmentioning
confidence: 78%
“…These CD8+ Ts cells (Ts2), or soluble proteins secreted by Ts2 cells (TsF2), directly inhibit the function of bulk populations of tubular antigen-specific CD8+ effector cells through a noncytotoxic mechanism ( 18,19). While the molecular definition of suppressor factors is still controver-sial, increasing evidence supports their being closely related to conventional TCR chains (21)(22)(23)(24).…”
Section: Introductionmentioning
confidence: 99%